Analisis Strategi Pemasaran Melalui Iklan Shopee untuk Meningkatkan Penjualan pada Usaha Mikro Buketku.bdg - Roshni Syavitri; Yose Andrea (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This research is motivated by the rapid growth of e-commerce in Indonesia and the dominance of the Shopee platform, which presents both opportunities and competitive challenges for MSMEs. The micro-business Buketku.bdg faced a decline in sales trends during the final quarter of 2025 despite utilizing paid advertising features. This study aims to analyze marketing strategies through Shopee Ads in increasing sales, using Kotler and Keller’s marketing management theory, which encompasses the marketing mix and Segmenting, Targeting, and Positioning (STP) strategies. The research method employed is a descriptive qualitative approach. Data were gathered through in-depth interviews with the business owner, employees, and customers, as well as direct observation and documentation studies of advertising performance. The findings indicate that the use of "Product Search Ads" with relevant keywords significantly increases product visibility to consumers. The results of the SWOT analysis place Buketku.bdg in a strong internal position to capitalize on seasonal graduation market opportunities through a Strength-Opportunity (S-O) strategy. The study concludes that the Shopee Ads strategy is effective in increasing sales when supported by precise product positioning, specifically production speed and premium embroidery quality.